Evacuation - Ishiwatari, Mikio; Arakida, Masaru (World Bank, Washington, DC, 2013)
Community evacuation measures should be the centerpiece of Disaster Risk Management (DRM) systems. Because the Sanriku region has suffered from frequent tsunamis, its local communities have passed their knowledge from generation to generation, mainly by constructing commemorative monuments and by conducting education and drills. Nevertheless, about 20,000 people died or are missing as a result of the catastrophic tsunami on March 11, 2011. Various factors, such as underestimating tsunami heights in warnings and on hazard maps, as well as a lack of awareness, influenced the number of human lives lost. Since neither the local governments nor the electric power company had prepared properly for possible nuclear accidents, evacuation from the accident at the Fukushima Daiichi nuclear power station was chaotic. Because predictions and other measures to foresee or prevent potential disasters are often unreliable, community evacuation measures should be at the center of DRM systems. Local governments conduct tsunami evacuation drills every year on days commemorating past large scale tsunamis, and residents learned how to evacuate safely and quickly from their own houses to designated shelters. Certain issues had been identified in evacuation measures even before the March 11 disaster. Public awareness about the possibility of a tsunami disaster had decreased since large-scale damage had not been sustained in many years.